Revitalisasi Kegiatan Kajian Rutin Masjid Al-Huda Gampong Laksana Sebagai Upaya Meningkatkan Partisipasi Jamaah - Siti Sara; Aida Rizkany Ash-Shofa; Khairul Habibi (Jurnal Kajian Manajemen Dakwah, 2026)
Mosques play a multifunctional role, but social and economic transformations have reduced participation in routine religious studies, especially in urban mosques. Al-Huda Mosque in Gampong Laksana, Banda Aceh City, experienced a similar phenomenon. Therefore, an in-depth study is needed to determine the inhibiting factors and revitalization strategies. This qualitative descriptive study identified the factors of decline and revitalization strategies through observations, interviews with the Community Empowerment Agency (BKM), congregation members, and documentation. The results showed that participation declined due to temporal conflicts with working hours, shifts in modern activities, and limited funds. The BKM responded by forming committees, making proposals, and intensifying da'wah (Islamic outreach). This study implies that adaptive mosque management based on congregation segmentation is necessary to maintain the relevance of da'wah amidst social and economic dynamics.